DOI: 10.11606/t.5.2014.tde-22092014-151937
|View full text |Cite
|
Sign up to set email alerts
|

Determinação de valores de referência para chumbo, cádmio, mercúrio e níquel em sangue de crianças e adultos da cidade de São Paulo

Abstract: Lista de Abreviaturas ALA-Enzima ácido δ-aminolevulínico sintetase ALAD-Enzima ácido δ-aminolevulínico desidratase

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 136 publications
(175 reference statements)
0
2
0
Order By: Relevance
“…To compare the effects of the mean blood Pb levels found in the DMN and CLA (control) districts, a search of the literature for the mean blood Pb levels reported in studies from several countries, including Brazil, was performed. Among individuals exposed to the industrialized environment in a region of China, a study reported that the mean Pb level was 157.47 μg·L −1 [12].…”
Section: Discussionmentioning
confidence: 99%
“…To compare the effects of the mean blood Pb levels found in the DMN and CLA (control) districts, a search of the literature for the mean blood Pb levels reported in studies from several countries, including Brazil, was performed. Among individuals exposed to the industrialized environment in a region of China, a study reported that the mean Pb level was 157.47 μg·L −1 [12].…”
Section: Discussionmentioning
confidence: 99%
“…Some Brazilian studies assessed exposure to toxic metals among blood donors and subjects from the general population. These studies measured blood concentrations of arsenic (As), lead (Pb), cadmium (Cd), manganese (Mn) [ 15 , 16 ], and Ni [ 17 ] in blood donors in the state of Acre; As, Pb, Cd, Cu, Mn, and mercury (Hg) in blood donors and young populations (children and adolescents) in São Paulo [ 18 , 19 , 20 , 21 , 22 ]; and cobalt (Co), As, Cu, Cr, Mn, Ni, Zn, Pb, and Cd in blood donors and the general population in the state of Paraná [ 23 , 24 ] and five other Brazilian states [ 25 ]. Few Brazilian studies investigated occupational exposure to toxic metals [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%